1992
DOI: 10.1073/pnas.89.23.11569
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-myristoyl protein switch.

Abstract: Recoverin, a recently discovered member of the EF-hand superfamily of Ca2+-bindig proteins, serves as a Ca2+ sensor in vision. The amino terminus of the protein from retinal rod cells contains a covalently attached myristoyl or related N-acyl group. We report here studies of unmyrtylated and myristoylated recombinant recoverin designed to delineate the biological role of this hydrophobic unit. Ca2+ induces the binding of both the unmyristoylated and myristoylated proteins to phenyl-agarose, a hydrophobic suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
307
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(323 citation statements)
references
References 29 publications
14
307
1
1
Order By: Relevance
“…Notably, the N-terminus of NCS proteins may play a critical role in post-translational modification and protein function: Proteins in classes A – D and the class E protein KChIP1 possess an N-terminal myristoylation sequence, and myristoylation of these proteins allows their membrane association [24,25]. Moreover, recoverin (class C) and all class B members of the NCS family exhibit a so-called Ca 2+ /myristoyl switch, meaning that the N-terminal myristoyl moiety, which is sequestered in a hydrophobic groove in the Ca 2+ -free state, swings out when the protein binds Ca 2+ [26,27]. In recoverin, which is a calcium sensor par excellence , this Ca 2+ -dependent conformational change allows the interaction with its target proteins (rhodopsin kinase and rhodopsin), and, at the same time, the association of the protein complex with the photoreceptor outer segment disc membrane (Figure 1A) to control light sensitivity in a Ca 2+ -dependent manner [28].…”
Section: The Ncs Protein Familymentioning
confidence: 99%
“…Notably, the N-terminus of NCS proteins may play a critical role in post-translational modification and protein function: Proteins in classes A – D and the class E protein KChIP1 possess an N-terminal myristoylation sequence, and myristoylation of these proteins allows their membrane association [24,25]. Moreover, recoverin (class C) and all class B members of the NCS family exhibit a so-called Ca 2+ /myristoyl switch, meaning that the N-terminal myristoyl moiety, which is sequestered in a hydrophobic groove in the Ca 2+ -free state, swings out when the protein binds Ca 2+ [26,27]. In recoverin, which is a calcium sensor par excellence , this Ca 2+ -dependent conformational change allows the interaction with its target proteins (rhodopsin kinase and rhodopsin), and, at the same time, the association of the protein complex with the photoreceptor outer segment disc membrane (Figure 1A) to control light sensitivity in a Ca 2+ -dependent manner [28].…”
Section: The Ncs Protein Familymentioning
confidence: 99%
“…Recently, the phospholipid/membrane binding domain of the plasma membrane Ca 2+ pump was shown to bind calmodulin (21). Several members of the EFhand superfamily, including calmodulin, are known to bind membranes or hydrophobic supports in the presence of calcium (19,63). Therefore, it seems possible that in vivo, this region represents a phospholipid/membrane binding site rather than a calmodulin-binding site.…”
Section: Iq Mo#mentioning
confidence: 99%
“…This mechanism is an induced change in the orientation of myristic acid from the hydrophobic interior of a protein to the hydrophobic interior of the plasma membrane, and it has been well described for recoverin, a myristylated cellular protein found in retinal rod cells (2,24,38,41). NMR structures of myristylated recoverin have shown that the myristyl group is buried in the center of a nonfunctional helix-loop-helix, the EF hand-like motif (38).…”
mentioning
confidence: 99%